2017
DOI: 10.1007/s12033-017-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Ability of T1 Lipase to Degrade Amorphous P(3HB): Structural and Functional Study

Abstract: An enzyme with broad substrate specificity would be an asset for industrial application. T1 lipase apparently has the same active site residues as polyhydroxyalkanoates (PHA) depolymerase. Sequences of both enzymes were studied and compared, and a conserved lipase box pentapeptide region around the nucleophilic serine was detected. The alignment of 3-D structures for both enzymes showed their active site residues were well aligned with an RMSD value of 1.981 Å despite their sequence similarity of only 53.8%. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…T1 lipase to degrade amorphous P(3HB) has also been suggested. 206 Thus examples presented in this section showed that the new screening and fundamental research analysis of known microbial lipolytic enzymes on PoE decomposition can be an objective for recent and future studies useful for plastic biodegradation.…”
Section: Enzymatic Degradation Of Polyurethanesmentioning
confidence: 98%
“…T1 lipase to degrade amorphous P(3HB) has also been suggested. 206 Thus examples presented in this section showed that the new screening and fundamental research analysis of known microbial lipolytic enzymes on PoE decomposition can be an objective for recent and future studies useful for plastic biodegradation.…”
Section: Enzymatic Degradation Of Polyurethanesmentioning
confidence: 98%
“…Using this method, lipases from bacteria, yeast, and animal origin were screened for degradation of poly (3-hydroxybutyrate-co-4hydroxybutyrate) [P(3HB-co-4HB)] and confirmed to degrade P(3HB-co-4HB) (Mok et al 2015). A lipase and depolymerase (PHZ7 Pl ), encoded by P. lemoignei, had a conserved amino acid consensus sequence for an oxyanion hole motif, as well as the catalytic triad sequence found in other PHA depolymerases (Mohamed et al 2017).…”
Section: R a F Tmentioning
confidence: 99%